Ready to Boost Adolescents’ Creative Thinking? How Problem-Based Blended Learning Empowers 15-17-Year-Old Students - Susilowati, Nur Endah; Okiri, Peter Ochieng; Efendi, Ridwan; Muslim, Muslim; Arifiyanti, Fitria; Saputra, M. Reza Dwi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Fostering creative thinking among teenagers in today’s fast-paced world is no longer optional but essential. As students navigate an era demanding innovation and problem-solving, teachers must rethink how learning happens. This study explores the effectiveness of problem-based blended learning (PBBL) in enhancing creative thinking skills among students aged 15-17. The study employs a quasi-experimental design involving both experimental and control groups, with a pre-test and post-test approach. A purposive sampling technique selected 40 students within the target age range. Students’ creative thinking was assessed using an essay-based instrument aligned with the PISA 2021 Creative Thinking Framework, which focuses on generating diverse ideas and creative ideas and evaluating and improving ideas. The results reveal that PBBL has a significant impact, as indicated by a high effect size tested using Cohen’s d formula of 0.9 on the post-test results. These findings suggest that problem-based blended learning is an effective strategy for promoting creative thinking skills in adolescents and may serve as a valuable approach for future educational practices.